(untitled) (Research, Society and Development, 2020)
This study compared the effects of unchopped and chopped hay on milk production and composition, feed digestibility, and physiology of Lacaune sheep. Eighteen ewes were stratified by parity (two or three), days of lactation (60 ± 3.7 days), and milk production (1.04 L/ewe/day), and were randomly assigned to 1 of 2 treatments: 1) Unchopped or 2) Chopped Tifton 85 hay. Corn silage and concentrate were also provided. Chopped hay ewes gave lower (P≤0.01) dry matter intake and greater (P=0.02) crude protein digestibility. No effects of treatment were detected (P≥0.38) for the digestibility of dry matter, or of neutral and acid detergent fibers. Chopped hay ewes had greater (P≤0.01) milk production (d 7 and d 12), lactation persistence, and feed efficiency. Ewes eating chopped hay had greater (P=0.03) protein concentration in their milk. However, there were no effects of treatment × day and treatments (P≥0.16) for concentrations of fat, lactose, minerals, deffated dry extract, or density. Ewes eating chopped hay presented lower (P<0.01) serum concentrations of urea and tended to have lower (P=0.10) serum concentrations of glucose only on d 12. However, there were no effects of treatment × day and treatments (P≥0.16) for serum concentrations of total protein, albumin, globulin, triglycerides, or cholesterol. These data suggest that chopped hay promotes lower dry matter intake and serum concentrations of glucose and urea, but improves milk production, lactation persistence, feed efficiency, and protein concentration.